In Sede Manium, Opes: Tracing the Funerary Use of Coinage in the Southern Italian Greek States Until the Pyrrhic War’s End - Zuckerman, Marshall (My University, 2024)
Missing from the discussion surrounding the use of coinage in select burials within southern Italian Greek necropoleis in the fourth and third centuries BCE is an attempt to reconstruct the ancient conception of the ritualistic function of coinage. It is through a chronological survey of epigraphical evidence for temple finances that we can trace the concurrent developments of the recognition of a fiduciary value to money, on one hand, and the acceptance of a ritualistic function to coinage on the other. Both occur simultaneously in Magna Graecia where the earliest coins in burial have been found. The case study of Metaponto, an archaeological site around the Lucanian Apennines, reveals a correspondence between an Oscan assemblage of funerary equipment and the presence of coinage. One tomb in particular contains an old coin’s ceramic impression, a clear representation of a value above that of its monetary model. Indigenous Italian agency ought therefore be considered when explaining, not just the ritualistic deposition of bronze coinage in Italy, but also a broader recognition of the sacred and fiduciary value to coinage which led to its deposition.
THE FUNERARY USE OF COINAGE IN SOUTHERN ITALIAN GREEK STATES
L’Utilisation funéraire de la monnaie en Grande-Grèce jusqu’à la fin de la guerre de Pyrrhus
Keywords: Economic history; Origin of money; History of economic thought; History of ideas; Funerary archeology; Magna graecia; Numismatics; Post-colonial studies; hybridity; Magna Grecia; Metaponto